Investigating the capital structure determinants of energy firms - Rehan, Raja (Edelweiss Applied Science and Technology, 2022)
The ongoing energy crisis has turned into a major bottleneck for economic growth and has had a long-lasting impact on the performance of energy firms. However, recognizing capital structure determinants helps these firms construct an ideal capital structure and attain their target of profitability. Thus, this study is an attempt to identify capital structure determinants for whole energy firms that are operating in dissimilar regions and countries. The 14-year balance panel data of 281 energy firms, i.e., 2007–2020, is used to perform the analysis. The debt-to-asset ratio is nominated as a dependent, whereas sales, current ratio, asset tangibility, non-debt tax shield, return on equity, inflation, gross domestic product, and energy consumption are selected as independent variables. The Panel Data Static models and Dynamic models via the Generalized Method of Moments (GMM) are executed to perform the inquiry. The results indicate that lagged dependent variables, sales, tangibility, return on equity, inflation, gross domestic products, and energy consumption are the main capital structure determinants of energy firms. The significant lagged dependent variable, tangibility, sales, and the existence of speed of adjustment point towards the practice of the Dynamic Trade-off theory by energy firms to maintain capital structure at all times. The results obtained by this empirical analysis are a new addition to the financial literature and will help policymakers develop similar policies regarding the capital structure-maintaining practices of energy firms that will enhance energy-related ties among countries.